Melangkah Bersama : Membangun Motivasi Belajar di SMP Sukamanah - Ageng Saepudin Kanda S.; Riki Yasa Putra (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
Based on field observations, there are still many students who have low learning motivation. However, there are quite a few who have high motivation to learn. Here the researcher analyzes 1). What makes learning motivation decrease? The second 2). How to increase learning motivation. The researcher's aim is to find out how much influence learning motivation has on students' futures. Researchers use quantitative methods in carrying out their analysis and observations. One of the reasons for the progress of a country is that it has high learning motivation, such as Finland. Hopefully the publication of this journal can increase student learning motivation, especially at my research site, Sukamanah Middle School. And schools everywhere can benefit. Also, high motivation to learn can increase one's electability and make the nation's children smarter.